a Practicality Test Of The Selected Topics Module In Artificial Intelligence As a Tool For Student-Led Self-Study - Maratus Shalihah; Mustari Lamada; Jumadi M Parenreng (Global Journal Basic Education, 2026)
This study aims to evaluate the practicality of the Selected Topics in Artificial Intelligence Module as a self-learning resource for students in the Computer Engineering Program at Makassar State University. This study employs the Research and Development (R&D) method using the 4-D development model, which includes define, design, develop, and disseminate. The research subjects consisted of 10 students in the small-group pilot test and 30 students in the large-group pilot test, as well as one lecturer in charge of the course. The research instrument was a practicality questionnaire that assessed three main indicators: content, media, and usefulness. The results of the practicality test showed that the lecturer’s assessment received an average score of 82% in the practical category. Meanwhile, the questionnaire results from 21 students showed an overall average score of 85% in the practical to very practical categories, specifically: content 85% (practical), media 88% (very practical), and utility 83% (practical). These findings indicate that the developed module is easy to use, enhances conceptual understanding, and supports students’ independent learning in the Artificial Intelligence Capita Selecta course. Thus, this module is deemed suitable and practical for use as a digital learning medium in higher education.